2017
DOI: 10.1002/bjs.10437
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the surgical management of complex intra-abdominal infection

Abstract: Background: Current guidance on the management of sepsis often applies to infection originating from abdominal or pelvic sources, which presents specific challenges and opportunities for efficient and rapid source control. Advances made in the past decade are presented in this article.Methods: A qualitative systematic review was undertaken by searching standard literature databases for English-language studies presenting original data on the clinical management of abdominal and pelvic complex infection in adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
1
10
0
4
Order By: Relevance
“… 19 With the increase in availability of cross-sectional imaging and interventional radiology, advances have been made in the diagnosis and nonoperative control of abdominal and pelvic collections, and the vast majority of patients can be controlled without early open surgery. 20 …”
Section: Initial Management Of Intestinal Failurementioning
confidence: 99%
See 1 more Smart Citation
“… 19 With the increase in availability of cross-sectional imaging and interventional radiology, advances have been made in the diagnosis and nonoperative control of abdominal and pelvic collections, and the vast majority of patients can be controlled without early open surgery. 20 …”
Section: Initial Management Of Intestinal Failurementioning
confidence: 99%
“…Rapid commencement in these patients once sepsis is confirmed is needed as there is good evidence to show a strong relationship between the timeliness of therapy and survival. 20 …”
Section: Initial Management Of Intestinal Failurementioning
confidence: 99%
“…Acute peritonitis is associated with high rates of morbidity and mortality, and careful control of the source of infection remains key to a successful treatment [8,23]. e use of minimally invasive surgical techniques, in particular percutaneous fluid drainage and laparoscopy, has been exceptionally valuable in cases of complex abdominal infections in patients with borderline physiological conditions such as diabetes, obesity, advanced age, and immunosuppression, where the negative impact of a laparotomy, although fundamental for the control of infection, may outweigh the benefit [23]. Although percutaneous drainage is feasible in most cases, some complex situations, such as unapproachable anatomical site or abscesses between loops, fistulas, and ischemic areas, require resection and catheter drainage is not practical [23].…”
Section: Discussionmentioning
confidence: 99%
“…e use of minimally invasive surgical techniques, in particular percutaneous fluid drainage and laparoscopy, has been exceptionally valuable in cases of complex abdominal infections in patients with borderline physiological conditions such as diabetes, obesity, advanced age, and immunosuppression, where the negative impact of a laparotomy, although fundamental for the control of infection, may outweigh the benefit [23]. Although percutaneous drainage is feasible in most cases, some complex situations, such as unapproachable anatomical site or abscesses between loops, fistulas, and ischemic areas, require resection and catheter drainage is not practical [23]. For these reasons, laparoscopic procedures have gained popularity among surgeons for the performance of difficult operations on patients with abdominal sepsis [8].…”
Section: Discussionmentioning
confidence: 99%
“…It is emphasized that abdominal sepsis is a result of both intraabdominal and retroperitoneal infections. [4][5] In a retrospective cohort study with patients diagnosed with sepsis and septic shock at a ICU in Rio Branco, Acre, it was identified that septic patients with a focus of abdominal infection presented the highest risk of death (HR: 3.71; 95% CI: 1.31-10.49) and 100% of these died at the end of 24 days of hospitalization. 6 In view of the problem, it is of paramount importance that health professionals are instrumented, aiming to collaborate, thus, in the care of the patient with sepsis of abdominal focus.…”
mentioning
confidence: 99%